Design and characterization of AgVO3-HAP/GO@PCL ceramic-based scaffolds for enhanced wound healing and tissue regeneration - Hagar M. Mahdy; Hanan Hendawy; Yehia M. Abbas; El-shazly M. Duraia (Journal of Materials Science: Materials in Medicine)
Abstract Rapid, infection-free wound healing remains a critical challenge in regenerative medicine. This study presents the fabrication and evaluation of multifunctional electrospun polycaprolactone (PCL)-based scaffolds incorporating silver vanadate (AgVO3), hydroxyapatite (HAp), and graphene oxide (GO) for advanced wound care applications. AgVO3 offers potent antibacterial properties, HAp supports osteogenic and regenerative activities and GO enhances both mechanical performance and cellular interactions. The scaffolds exhibited a highly porous nanofibrous structure, mimicking the extracellular matrix (ECM) and promoting cell attachment, migration, and nutrient exchange. Comprehensive physicochemical characterization using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), Raman spectroscopy, and field-emission scanning electron microscopy (FE-SEM) confirmed the successful integration of the composite. Mechanical testing revealed that GO-containing scaffolds significantly improved stiffness, with AgVO3/GO@PCL and HAp/GO@PCL achieving Young’s moduli of 5.82 MPa and 4.36 MPa, respectively, which are substantially higher than that of neat PCL (1.39 MPa). In terms of flexibility, HAp/GO@PCL displayed the highest elongation at break (107.54%), indicating exceptional stretchability. The ultimate tensile strength was also enhanced in HAp@PCL (0.80 kJ/m3) and AgVO3/@PCL (0.88 kJ/m3), highlighting their capacity to resist mechanical stress during application. Contact angle measurements showed that the AgVO3-HAp/GO@PCL scaffold had the highest hydrophilicity (65.58° ± 5.97), compared to pure PCL (89.89° ± 3.70), indicating improved wettability, which is critical for fluid management and cell-material interactions at the wound interface. In vivo wound healing studies using a full-thickness rat model demonstrated that AgVO₃/GO@PCL scaffolds achieved 50% wound closure within 3 days, while AgVO₃-HAp/GO@PCL scaffolds facilitated complete re-epithelialization by day 14. Histological analysis confirmed enhanced collagen deposition and organized tissue architecture. The scaffolds also exhibited strong antibacterial activity, with large inhibition zones against S. aureus and E. coli. These findings position AgVO₃-HAp/GO@PCL scaffolds as promising candidates for next-generation wound dressings, offering a robust combination of mechanical resilience, bioactivity, antimicrobial efficacy, and moisture balance tailored for clinical wound-healing applications. Graphical Abstract